Utopia, carnival, and commonwealth in Renaissance England - Kendrick, Christopher, 1953- (Toronto ; Buffalo : University of Toronto Press, 2004)
With the emergence of utopia as a cultural genre in the sixteenth century, a dual understanding of alternative societies, as either political or literary, took shape. In Utopia, Carnival, and Commonwealth in Renaissance England, Christopher Kendrick argues that the chief cultural-discursive conditions of this development are to be found in the practice of carnivalesque satire and in the attempt to construct a valid commonwealth ideology. Meanwhile, the enabling social-political condition of the new utopian writing is the existence of a social class of smallholders whose unevenly developed character prevents it from attaining political power equivalent to its social weight. In a detailed reading of Thomas More's Utopia, Kendrick argues that the uncanny dislocations, the incongruities and blank spots often remarked upon in Book II's description of Utopian society, amount to a way of discovering uneven development, and that the appeal of Utopian communism stems from its answering the desire of the smallholding class (in which are to be numbered European humanists) for unity and power. Subsequent chapters on Rabelais, Nashe, Marlowe, Bacon, Shakespeare, and others show how the utopian form engages with its two chief discursive preconditions, carnival and commonwealth ideologies, while reflecting the history of uneven development and the smallholding class. Utopia, Carnival, and Commonwealth in Renaissance England makes a novel case for the social and cultural significance of Renaissance utopian writing, and of the modern utopia in general.
Utopian Differences -- Defining Middles: Morris, Fourier, Marx -- Defining Beginnings: Utopia -- Carnival and Utopia -- Utopia as the Negation of Carnival -- Carnival Strikes Back: Rabelais's Abbey of Theleme -- Utopia and the Commonwealth -- Conjuring Revolution in the Dialogue of Counsel -- The Body Politic and Utopia in A Dialogue of Pole and Lupset -- A Discourse of the Commonweal, the East Anglian Rebellion, and the End of the Smallholding Utopia -- Sprung Desire and Groups in Flux: On the Politics of the Utopian Impulse in Marlowe and Shakespeare -- Travesty, Allegory, and the Political Effectivity of Renaissance Drama -- Marlowe and the Utopia of Sprung Desire -- Groups in Flux in Shakespeare's Henry IV, Part I -- Flights from the Tudor Settlement; or, Carnival and Commonwealth Revised -- Nashe's Lenten Utopia -- The Imperial Lab: Discovering Forms in The New Atlantis.
Includes bibliographical references and index.
JSTOR
Keywords: More, Thomas, -- Saint, -- 1478-1535 -- Influence; More, Thomas, -- Saint, -- 1478-1535.; More, Thomas, -- Saint, -- 1478-1535; Utopia (More, Thomas, Saint); English literature -- Early modern, 1500-1700 -- History and criticism; Utopias in literature; Politics and literature -- Great Britain -- History -- 16th century; Politics and literature -- Great Britain -- History -- 17th century; Satire, English -- History and criticism; Imaginary societies in literature; Carnival in literature; Renaissance -- England; Littérature anglaise -- 1500-1700 (Moderne) -- Histoire et critique; Utopies dans la littérature.; Politique et littérature -- Grande-Bretagne -- Histoire -- 16e siècle.; Politique et littérature -- Grande-Bretagne -- Histoire -- 17e siècle.; Carnavals dans la littérature.; Renaissance -- Angleterre; utopian literature; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; HISTORY -- Renaissance; Carnival in literature; English literature -- Early modern; Imaginary societies in literature; Influence (Literary, artistic, etc.); Politics and literature; Renaissance; Satire, English; Utopias in literature; England; Great Britain; Literatur; Utopie; Utopia (More); Utopieën.; Englisch; 1500-1700; Geschichte 1549-1660.; Electronic books; Criticism, interpretation, etc; History